Relationships between phyllotaxis and agronomic performance among dura parents and its selfed progenies in oil palm - Abdullah, Norziha; Yusop, Mohd Rafii; Din, Ahmad Kushairi; Amiruddin, Mohd Din (2009)
Relationships of 30 selfed oil palm dura progenies and its parents were analysed based on phyllotaxis. 48 palms per progeny were involved and planted in 3 replicates.The data collected were the type of phyllotaxis, bunch yield and bunch quality characters. The t-test showed no differences for number of palms between the right- and left-handed phyllotaxis among the dura progenies. From the analysis of variance (ANOVA), non-significant differences for phyllotaxis, and progeny x phyllotaxis interaction items were observed for all the yield and bunch quality characters. This suggested that there was no influence of phyllotaxis on the yield and bunch quality characters of the oil palm population. Heritability estimates for bunch yield and bunch quality characters were low to moderate, ranging from 6.59% to 38.04%. Five characters, average bunch weight (ABW), kernel to fruit ratio (K/F), oil yield (OY), total oil (TOIL) and total economic product (TEP) showed higher heritability values for the right-handed phyllotaxis, whereas the other five characters, fresh fruit bunch (FFB), bunch number (BNO), mesocarp to fruit ratio (M/F), shell to fruit ratio (S/F) and oil to bunch ratio (O/B) showed the opposite trend. This indicated that phyllotaxis did not significantly influence the heritability estimates among the characters.